Managing the functional diversity of arbuscular mycorrhizal fungi for the sustainable intensification of crop production - Brito, Isabel (2021)
Despite the wide range of benefits arbuscular mycorrhiza can confer, they are not usually considered in large-scale farming systems because the potential improvements in crop yields through the enhanced uptake of nutrients is a matter of debate and the advantages from the bio- protection afforded against biotic and abiotic stresses have not been adequately recognised. Research carried out by our group over the last 20 years has allowed the development of a strategy based on the intentional use of selected host plants (Developer plants), to develop an extensive extraradical mycelium which, when kept intact by the adoption of appropriate tillage techniques, acts as preferential source of inoculum for the following crop, leading to earlier and faster colonization by AM fungi. Depending on the particular host plant chosen as Developer, this strategy can also be used as a tool to manage AMF functional diver-sity. Using this approach, we have achieved effective protection against abiotic (Mn soil toxicity) and biotic (Fusarium oxysporum and Magnaporthiopsis maydis) stresses in different crops. The strategy can easily be applied at field scale, both in low and high input cropping systems. It only requires small changes to the cropping system, such as employing no-till and altered crop rotation or cover crops, that are simple to adopt and can realistically be implemented at the field level. This represents an important breakthrough as it allows intentional and predictable manipulation of the native soil mycorrhizal population over a range of different soils and circumstances.